Making sense of Artificial Intelligence (AI) in education: Enhancing teachers’ agency through knowledge, competence, and trust in using AI - Nur Syamsiyah; Claudia Anridho; Pingkan Sekar Savira; Ratna Azis Prasetyo; Rafi Aufa Mawardi; Armand Nicod-am Camhol (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2026)
This research explores teachers’ preparedness to incorporate artificial intelligence (AI) into education by examining the mediatory role of knowledge, competence, and trust in developing teacher agency. This research was conducted at MAN 2 Ngawi through observation, Focus Group Discussions (FGDs) and reflective narratives written by 55 participating teachers. The findings show that teachers’ knowledge of AI initially operates at a functional level, primarily associated with efficiency in administrative tasks. However, through training and collaborative reflection, this understanding evolves into a more critical awareness of ethical issues which include bias and inacurracy. Teachers’ competence is shaped by technical skills, adaptability, social interaction as well as contextual conditions. Therefore, competence is seen as both technical and social capital. Meanwhile, trust emerges as the most dynamic and contested dimension. Although some teachers acknowledge the benefits of AI, their trust remains conditional and influenced by their concerns over reliability, ethical implications, and the opacity of AI systems. This research further highlights that the enhancement of teachers’ agency lies in knowledge, competence, and trust that facilitate teachers’ exercise of autonomy and critical development of technology integration in education.